2007
DOI: 10.2337/db06-1687
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Fat Oxidation After a Single High-Fat Meal in Insulin-Sensitive Nondiabetic Individuals With a Family History of Type 2 Diabetes

Abstract: Individuals with insulin resistance and type 2 diabetes have an impaired ability to switch appropriately between carbohydrate and fatty acid oxidation. However, whether this is a cause or consequence of insulin resistance is unclear, and the mechanism(s) involved in this response is not completely elucidated. Whole-body fat oxidation and transcriptional regulation of genes involved in lipid metabolism in skeletal muscle were measured after a prolonged fast and after consumption of either high-fat (76%) or high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 50 publications
(45 reference statements)
1
47
2
Order By: Relevance
“…These findings are consistent with recent observations that increased lipid levels are associated with neuropathy (Callaghan et al, 2012) possibly by oxLDL interaction with the receptor LOX-1 (Vincent et al, 2009; Wiggin et al, 2009). Impaired fatty acid oxidation is strongly correlated to impaired activation of PGC-1α (Heilbronn et al, 2007) and adipose-specific ablation of PGC-1α results in Mt dysfunction (Kleiner et al, 2012). Thus, Mt PGC-1α has a critical role in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with recent observations that increased lipid levels are associated with neuropathy (Callaghan et al, 2012) possibly by oxLDL interaction with the receptor LOX-1 (Vincent et al, 2009; Wiggin et al, 2009). Impaired fatty acid oxidation is strongly correlated to impaired activation of PGC-1α (Heilbronn et al, 2007) and adipose-specific ablation of PGC-1α results in Mt dysfunction (Kleiner et al, 2012). Thus, Mt PGC-1α has a critical role in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Poorly controlled T2D subjects also display reduced net limb fat oxidation (by indirect calorimetry) [97]. Reduction of muscle oxidative phosphorylation and substrate oxidation was found in IR offspring of parents with T2D [4, 98,99]. Muscle mitochondria in IR or T2D are smaller and display reduced fatty acid oxidation in some [95], but not all, studies [84,87].…”
Section: Abnormal Lean Tissue Fatty Acid Metabolismmentioning
confidence: 97%
“…We and others 57 have also reported that these individuals have an impaired ability to respond to dietary 58 challenge, including impaired fatty acid oxidation in response to a single high fat meal [10] or 59 3-days isocaloric high fat feeding [11].…”
mentioning
confidence: 99%